2003
DOI: 10.1007/s00204-003-0501-8
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and oxidative stress induced by ochratoxin A in rat kidney

Abstract: Ochratoxin A (OTA) is a widespread mycotoxin produced by several species of fungi. OTA induces a tubular-interstitial nephropathy in humans and in animals. It has been implicated as one of the aetiological agents involved in the development of endemic nephropathy. OTA-induced oxidative stress and apoptosis may play key roles in the development of chronic tubulointerstitial nephritis connected to the long-term exposure to this food contaminant. We studied the effects of low doses of OTA on kidney cells. Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 41 publications
7
71
2
Order By: Relevance
“…In vitro and in vivo data suggest an involvement of oxidative stress in OTA-mediated cytotoxicity [1,4,16,17,23,30]. In fact, we observed in kidney tubulus cells a significant increase in reactive oxygen species production after OTA treatment already at relatively low OTA concentrations (0.5-2.5 lmol/L) [5] which were similar to those concentrations we used in the present study in neurons.…”
Section: Discussionsupporting
confidence: 89%
“…In vitro and in vivo data suggest an involvement of oxidative stress in OTA-mediated cytotoxicity [1,4,16,17,23,30]. In fact, we observed in kidney tubulus cells a significant increase in reactive oxygen species production after OTA treatment already at relatively low OTA concentrations (0.5-2.5 lmol/L) [5] which were similar to those concentrations we used in the present study in neurons.…”
Section: Discussionsupporting
confidence: 89%
“…Some authors did not find any apoptotic cells in the kidney of OTA-treated animals (Mantle et al 1998) while others obtained results compatible with the presence of apoptosis (WHO 2001, O'Brien andDietrich 2005). For example, using the TUNEL assay, apoptotic cells were observed in rats given OTA (120 mg/kg bw/day) for 60 days (Petrik et al 2003). However, in this study, DNA electrophoresis did not show any characteristic fragmentation (DNAladdering).…”
Section: Apoptosiscontrasting
confidence: 43%
“…For example, an increased formation of the lipid peroxidation product malondialdehyde (MDA) was observed in rats treated orally with 120 mg/kg bw/day of OTA over 60 days (Petrik et al 2003). In cell culture, an OTA-dependent increase in DNA damage (such as formation of 8-oxoguanine) was correlated with a production of reactive oxygen species (Schaaf et al 2002, Kamp et al 2005.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Increased malondialdehyde (MDA) production, indicating LPO increase, was reported earlier in vitro [33]. Petrik et al (2003) demonstrated that a very low concentration of ochratoxin was sufficient to induce apoptosis and oxidative damage to kidney cells in Wistar rats [34].…”
Section: Discussionmentioning
confidence: 72%